2022
DOI: 10.18196/jesp.v23i1.13198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monetary Instrument of Islamic Banking Financing Channel Towards The Economic Growth in Indonesia

Abstract: Monetary policy is closely related to activities to achieve economic growth, which eventually gives welfare to the community. This study aims to analyze the description of the transmission flow of financing channels, the effect of monetary policy instruments, and their effectiveness to achieve economic growth. The variables used are Islamic Banking Finance (FIN), return of Sharia Bank Indonesia Certificate (SBIS), return of PUAS, and Industrial Production Index (IPI). This study used Vector Error Correction Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Perform a stationarity test utilizing the root test (unit root test) and the Augmented Dickey-Fuller Test (ADF test) method to determine whether one of the assumptions in the time series data test using the VECM model analysis is true. Non-stationary data results in false regression, a regression that describes the relationship between two or more statistically significant visible variables, when it is not (Johari et al, 2022). The results are as follows: Determinants of short and long-term exchange market pressure in Indonesia For all stationary variables in the results mentioned above, Table 2 displays the outcomes of the unit root at the first difference level.…”
Section: Stationarity Testmentioning
confidence: 99%
“…Perform a stationarity test utilizing the root test (unit root test) and the Augmented Dickey-Fuller Test (ADF test) method to determine whether one of the assumptions in the time series data test using the VECM model analysis is true. Non-stationary data results in false regression, a regression that describes the relationship between two or more statistically significant visible variables, when it is not (Johari et al, 2022). The results are as follows: Determinants of short and long-term exchange market pressure in Indonesia For all stationary variables in the results mentioned above, Table 2 displays the outcomes of the unit root at the first difference level.…”
Section: Stationarity Testmentioning
confidence: 99%
“…Most of the previous studies implement the aggregate macroprudential policy indicators (Ćehajić & Košak, 2022;Gaganis et al, 2020). Other studies use the central bank reserve requirement to represent prudential capital requirements affecting bank financial intermediations (De Schryder & Opitz, 2021;Fabiani et al, 2022;Igan et al, 2022;Johari et al, 2022). Another complete implementation of disaggregate macroprudential indicators focused on implementing each instrument on banks profit earnings (Davis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The interest rate is one variable affecting inflation (Kurniawan et al, 2022). The interest rate is one of the main instruments for monetary policy conducted by central banks (Arintoko & Kadarwati, 2022;Johari et al, 2022). Sulistiana et al (2017) found that the interest rate, proxied by the BI rate (interest rate targeted by the Indonesian central bank), is the most dominant factor that affects inflation.…”
Section: Introductionmentioning
confidence: 99%